Pengaruh Beban Kerja dan Burnout terhadap Kinerja Karyawan melalui Stress Kerja sebagai Variabel Intervening pada Kantor Pegadaian Cabang Tarandam Kota Padang - Azura Mukzizah; Aminar Sutra Dewi (ARZUSIN, 2026)
The issue of declining employee performance in financial service organizations has become increasingly salient when linked to workload and burnout, which have the potential to heighten job stress, while studies that specifically position job stress as an intervening variable in the relationship between workload, burnout, and employee performance in the context of state-owned pawn service enterprises remain limited. This study aimed to analyze the effect of workload and burnout on employee performance through job stress as an intervening variable at the Pegadaian Branch Office of Tarandam, Padang City. A quantitative approach with a survey design was employed, involving 40 employees selected using a total sampling technique. Data were collected using Likert-scale questionnaires and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that workload did not have a significant effect on employee performance, whereas burnout and job stress had a significant negative effect on performance. In addition, workload and burnout had a significant positive effect on job stress, and job stress was found to mediate the effect of both variables on employee performance. These findings reinforce job stress theory and underscore that controlling burnout and job stress is a key factor in maintaining and enhancing employee performance in state-owned financial service organizations. The practical implications suggest that management should design workload management policies and sustained psychological intervention programs to minimize job stress and burnout so that employee performance can be optimally maintained. Keywords: Workload; Burnout; Job Stress; Employee Performance; SEM-PLS